Estimating running safety factor of ballastless railway bridges using tail modelling - Reza Allahvirdizadeh; Andreas Andersson; Raid Karoumi (Acta Polytechnica CTU Proceedings)
Excessive vertical acceleration of ballastless railway bridges subjected to vibrations induced by passing trains is one of the governing design criteria for bridges in high-speed lines. However, to the authors’ knowledge, the corresponding design limit is not based on a solid theoretical or experimental background. Moreover, the traditionally applied safety factor also suffers from these concerns. Therefore, in the present study, a crude probabilistic approach is adopted to evaluate the consistency and reliability of this safety factor. For this purpose, deterministically designed bridges (using conventional methods) with short to medium spans are considered. Then, their reliability is evaluated using simulation-based techniques and extreme value theory, i.e., tail approximation. Then, the existing safety factor is calculated to evaluate the consistency of the current approaches, and possible new values are proposed based on the desired target reliabilities.